“Para que nunca más sea”: O Memorial da Democracia e a Pedagogia da Memória - Antônio Fernando de Araújo Sá (Les Cahiers ALHIM)
The purpose of this article is to report on the process of building the Memorial of Democracy at the Federal University of Sergipe in the context of disputes over memories about the military dictatorship in Brazil (1964-1985) during the fiftieth anniversary of the 1964 coup d'état. As a place of memory, his proposal seeks to articulate the concepts of truth, memory, justice and human rights, as a manifestation of disagreement with the policy of forgetting established during the transition to democracy in Brazil. In addition to a space for social coexistence, consolidated by the architectural project, the memorial proposes to establish a pedagogy of memory, interconnecting public lessons and artistic manifestations in the construction of a democratic narrative about the right to citizenship.